1994
DOI: 10.1111/j.1365-2222.1994.tb00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Airborne birch pollen antigens in different particle sizes

Abstract: Two particle samplers for ambient air, situated together: a static size-selective bio-aerosol sampler (SSBAS) and a Burkard pollen and spore trap were compared in sampling intact birch pollen grains through one flowering period of Betula (a total of 44 days). The SSBAS trapped pollen grains three times more efficiently than the Burkard trap, but the variations in pollen counts were significantly correlated. In contrast, birch pollen antigenic activity and the pollen count in the Burkard samples were not closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 24 publications
5
77
1
1
Order By: Relevance
“…This shows that the only source of allergen is birch pollen, in agreement with previous results where allergens were monitored for several years on a row at one location (Buters et al, 2010). Birch allergen containing particles were reported in the fractions PM < 10 mm (birch pollen have a geometric diameter of 21e24 mm (Brown and Irving, 1973;Rantio-Lehtimäki et al, 1994;Schäppi et al, 1999)) indicating in combination with our results that if such particles exist, their appearance is rare and might need specific atmospheric conditions like thunderstorms (D'Amato et al, 2008), which did not occur during our experiments.…”
Section: Allergen Bet V 1 In Ambient Airsupporting
confidence: 91%
“…This shows that the only source of allergen is birch pollen, in agreement with previous results where allergens were monitored for several years on a row at one location (Buters et al, 2010). Birch allergen containing particles were reported in the fractions PM < 10 mm (birch pollen have a geometric diameter of 21e24 mm (Brown and Irving, 1973;Rantio-Lehtimäki et al, 1994;Schäppi et al, 1999)) indicating in combination with our results that if such particles exist, their appearance is rare and might need specific atmospheric conditions like thunderstorms (D'Amato et al, 2008), which did not occur during our experiments.…”
Section: Allergen Bet V 1 In Ambient Airsupporting
confidence: 91%
“…The presence of fragments was confirmed by SEM observations. The presence of airborne fragments is clearly documented with pollen exposures, as the onset of seasonal allergies is shown to start several weeks before the respective pollen grains are detected in the air (43,52). In contrast, the role of fragments in fungal exposures has not been sufficiently recognized.…”
Section: Discussionmentioning
confidence: 94%
“…The principal new finding reported here is that fungal fragments are released together with spores from contaminated surfaces. While the presence of fragments is docu-mented with pollen exposures (43,52), fungal fragments have gained much less attention. The role of fungal fragments is particularly interesting in the light of recent epidemiological studies on the relationship between outdoor air particulate pollution and health effects.…”
mentioning
confidence: 99%
“…It is also a period of atmospheric instability in the Mediterranean area, characterized by storms and heavy rainfall, sometimes over 50mm/day. As suggested earlier, this may lead to the disruption and alteration of some pollen grains, giving rise to paucimicronic particles with allergenic activity (Spieksma et al [12], Rantio-Lehtimaki et al [13]). Although the methods used here could not confirm the presence of such paucimicronic particles in the < 10 micron fraction, other authors measuring the potential allergenic activity of non-pollen airborne particles report intense activity following the Olea pollination period in particles of ≤ 3.3 microns (De Linares et al [14]).…”
Section: Discussionmentioning
confidence: 99%
“…Paucimicronic allergen particles measuring less than 2.5 microns have been detected in air quality tests (Spieksma et al [12], Rantio-Lehtimaki et al [13], De Linares et al [14]), and research has shown that pollen grains are the major cause of deterioration of biological air quality (Cariñanos et al [15]). …”
Section: Introductionmentioning
confidence: 99%